Physical activity among older Chinese adults living in urban and rural areas: A review - Wenfei Zhu; Aiping Chi; Yuliang Sun (Elsevier, 2016)
With an increase in rural-to-urban migration, a rapidly aging population, and the rising risk of developing noncommunicable diseases in China, it is important to understand the epidemiology of physical activity (PA) and health in the context of disease prevention and population health. Despite its public health importance, there is a significant lack of knowledge about PA in older Chinese adults that may hamper primary prevention efforts of health promotion in an increasingly aging population. To fill this gap, this article presents a narrative review of PA in the older Chinese adult population with a special focus on residential settings (i.e., urban and rural). Using existing studies, the review examines overall PA patterns and their correlates and discusses public health implications and future research. Although there are some preliminary indications of urban and rural differences in PA in the aging population in China, continued research efforts are needed to facilitate primary prevention efforts aimed at reducing noncommunicable diseases and promoting an active lifestyle among the largest population of older people in the world.